Exploring the application of mixed reality in Nurse education. (21st August 2019) - Frost, Jane; Delaney, Lori; Fitzgerald, Robert
Abstract : The aim of this study was to explore the contemporary application, inclusive of advantages and challenges, of mixed reality (MR) technology in the education of nursing students and, its contribution to enhanced learning. A descriptive evaluation design was undertaken to explore the learning experience of second year students enrolled in a 3 year Bachelor of Nursing programme. One hundred per cent of the students stated that the experience assisted them in their learning. The key themes of engagement in learning, and developing clinical judgement emerged from students' responses, and demonstrated ways in which students felt MR enhanced their learning. This emerging technology has the potential to assist in enhancing clinical judgement and developing skills in noticing physical cues in patients. The implementation of MR may also enhance student motivation and engagement with learning.